Daratumumab treatment for kidney-involved light chain deposition disease prevents renal function progression: a case report with 3 years of follow-up and review of the literature - Chen, Xueying; Sun, Jie; Shen, Pingyan; Chen, Zijin; Zhang, Wen (Frontiers in Oncology, 2025)
Light chain deposition disease (LCDD) is a clonal plasma cell disorder characterized by the deposition of nonamyloid monoclonal light chains in multiple organs. It can affect various systems throughout the body, mainly the kidneys. Symptoms may include renal insufficiency, proteinuria, hematuria, and others. Due to the lack of effective treatment, LCDD patients with kidney involvement often progress to chronic kidney failure, ultimately requiring renal replacement therapy. Daratumumab, an anti-CD38 monoclonal antibody, is primarily used for the treatment of relapsed and refractory multiple myeloma. Recent studies have shown that daratumumab also has an encouraging effect on light-chain amyloidosis. Here, we report the case of an LCDD (κ chain) patient with proteinuria, renal insufficiency, and anemia who was followed up for 3 years, during which he received daratumumab treatment. After the daratumumab treatment, the hematologic response continued progressing to a complete response without any adverse effects and continuous renal function improvement at a low serum free light chain (sFLC) level. This case shows that daratumumab is effective at treating LCDD. For LCDD patients with kidney involvement, frequent monitoring and active control of free light chain levels are necessary, as reaching the lowest sFLC of < 20 mg/L may help to improve kidney function.